Multi-objective optimization and linear buckling of serial chain of a medical robot tool for soft tissue surgery - Ilewicz, Grzegorz; Harlecki, Andrzej (IAES International Journal of Robotics and Automation (IJRA), 2020)
The slender structures of a medical robot may have a tendency to buckling when a force equal to the critical Euler force and an additional disturbance will work on their structures. In this work, eigenvalue problem that describes the linear buckling is under consideration. The main goal of the article is to check when linear buckling phenomenon appears in construction of a medical robot with serial chain due to the fact that for safety reasons of a robot’s work, it is necessary to answer the question, whether the buckling may occur in the robot’s structure. For this purpose, a numerical calculation model was defined by using the finite element method. The values of load factor coefficients that are eigenvalue are determinated and also the eigenvectors that have shapes of deformation for the next eigenvalues are presented. The multi-criteria optimization model was determined to aim for the minimum mass of the effector and the buckling coefficient, from which the Euler force results, for the maximum. The solution was obtained on the basis of Pareto fronts and the MOGA genetic algorithm.